The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/0011000013477903
|View full text |Cite
|
Sign up to set email alerts
|

Mexican-Origin Early Adolescents’ Ethnic Socialization, Ethnic Identity, and Psychosocial Functioning

Abstract: The current study examined how parental ethnic socialization informed adolescents’ ethnic identity development and, in turn, youths’ psychosocial functioning (i.e., mental health, social competence, academic efficacy, externalizing behaviors) among 749 Mexican-origin families. In addition, school ethnic composition was examined as a moderator of these associations. Findings indicated that mothers’ and fathers’ ethnic socialization were significant longitudinal predictors of adolescents’ ethnic identity, althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 64 publications
7
82
1
Order By: Relevance
“…For girls, one possible explanation for the null findings is that they may have other salient experiences at play that inform their engagement in ERI exploration. For example, research has shown that adolescents’ ERI exploration is related to the cultural socialization messages they receive from their families (Supple, Ghazarian, Frabutt, Plunkett, & Sands, ; Umaña‐Taylor, O'Donnell, et al., ), and that this relation is particularly strong among women (Juang & Syed, ), and may be especially salient among Mexican‐origin adolescent mothers who are relying heavily on their own mothers for support during early parenthood (Contreras, Narang, Ikhlas, & Teichman, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For girls, one possible explanation for the null findings is that they may have other salient experiences at play that inform their engagement in ERI exploration. For example, research has shown that adolescents’ ERI exploration is related to the cultural socialization messages they receive from their families (Supple, Ghazarian, Frabutt, Plunkett, & Sands, ; Umaña‐Taylor, O'Donnell, et al., ), and that this relation is particularly strong among women (Juang & Syed, ), and may be especially salient among Mexican‐origin adolescent mothers who are relying heavily on their own mothers for support during early parenthood (Contreras, Narang, Ikhlas, & Teichman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Discrimination is a common experience for ethnic–racial minority youth in the United States (Umaña‐Taylor, ) and has been consistently linked to adverse mental and physical health outcomes (Pascoe & Smart Richman, ). Ethnic–racial identity (ERI) formation, a central aspect of positive youth development that is particularly salient during adolescence (Spencer, ; Swanson, Spencer, dell'Angelo, Harpalani, & Spencer, ; Umaña‐Taylor, O'Donnell, et al., ; Umaña‐Taylor, Quintana, et al., ; Williams, Tolan, Durkee, Francois, & Anderson, ), has been found to relate to adolescent well‐being and, in some instances, has been found to buffer the adverse effects of discrimination (see Marks, Ejesi, McCullough, & García Coll, for an overview). Few studies, however, have focused on the interrelation and bidirectional associations of ERI and discrimination, limiting our knowledge about how these two salient constructs may co‐occur and affect one another over time.…”
Section: Theoretical Framework Linking Discrimination and Erimentioning
confidence: 99%
“…This pattern suggests that growing up in a family with higher levels of cultural socialization may have sensitized youth to differential treatment, making them more reactive to its effects. In prior research, cultural socialization has proven to promote Mexican-origin youth’s well-being, as youth build stronger identities with and see themselves as members of their cultural group (Umaña-Taylor, O’Donnell, Knight, Roosa, Berkel, & Nair, 2014). Siblings with less favored status (i.e., more conflict/less warmth relative to siblings) from families high in cultural socialization may be most negatively affected by PDT because they see themselves as devalued—by someone who is an important figure for their identity formation.…”
Section: Discussionmentioning
confidence: 99%
“…Related research findings suggest that the promotive effect of ethnic socialization on youth outcomes is mediated by a strong ethnic identity (Gartner, Kiang, & Supple, 2014;Mohanty, 2013;Umaña-Taylor et al, 2014). They also highlight the promotive benefit of ethnic identity that provides youth with confidence and a positive self-concept, which contribute to improved school achievement and life satisfaction.…”
Section: Theoretical Frameworkmentioning
confidence: 91%